PENGUATAN PENGETAHUAN MENGENAI BULLYING UNTUK ANAK SEKOLAH DASAR GMIH DAEO MALUKU UTARA - Sabban, Irawati; Jaguna, Fahmi (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
Bullying is a pattern of aggressive behavior, the most vulnerable children face a higher risk of being bullied. The Halmahera Christian Church (GMIH) Elementary School is located in Daeo Village, South Morotai District. As a school under the Ministry of Religion which is located in a Muslim-majority environment, it does not alienate the school community because the school has Muslim teachers and accepts Muslim students. Bullying education is appropriate for children from marginalized communities, children with different gender identities, these criteria are what moved us to create outreach activities about bullying so that religious harmony is maintained. The implementation method is by socializing and playing games to train cohesiveness between teams. The results of the activity provide an understanding of bullying, the impact on friends, and respect for differences. The principal and teachers were also very enthusiastic and received us very well, they hope that activities like this will not only happen once but repeatedly.